DEVELOPMENT OF PROBLEM BASED LEARNING MODEL ASSISTED BY QUIZIZZ ON ECONOMIC SOCIAL STUDIES AT JUNIOR HIGH SCHOOLS - Ramero Saragi; Joko Widodo; Fahrur Rozi (Journal of Economic Education, 2026)
Problem Based Learning is a suitabled educational model for the complex economics social studies. However, in practice, teachers in schools seldom develop this model to meet the unique characteristics and learning needs of students. Additionally, the implementation of interactive learning media is also crucial to increase the effectiveness of the model. Based on the reasons, this study attempts to develop the implementation development of Problem Based Learning model asissted by Quizizz on economics social studies at junior high schools. This study used a qualitative approach by Research and Development (R&D) method through the 4D research stages (define, design, develop, and disseminate). This study was conducted at National JHS 32 Semarang, focus on the 9th grade. The limited experiment was done in a class with 30 students and the next experiment was done in two class which also have 30 student each. The instruments in this study include observations, interview, and questionaries. In addition, the validity of data is tested using the data triangulation techniques. The research finding focused on developing the Problem Based Learning syntax and integrating the Quizizz as an auxiliary model. According to the validity questionnaire assessment, the average feasibility assessment for development products was 91% (Very Good) and 9% (Good). Meanwhile, student satisfaction responses to development were 98% (Strongly Agree) and 2% (Agree). Thus, the Problem Based Learning model assisted by Quizizz was declared worthy of dissemination. Based on the finding of this studies, the use of the Problem Based Learning Model assisted by Quizizz needs to be adjusted to the students' characteristics and learning needs in order to maximize the learning outcomes. Besides, the teachers could redevelop the research products by integrating other interactive learning media to boost the effectiveness of the Problem Based Learning model.